2018
DOI: 10.1007/s11356-018-2235-4
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling motor behaviour hallmarks in intoxicated adolescents: methylmercury subtoxic-dose exposure and binge ethanol intake paradigm in rats

Abstract: Methylmercury (MeHg) is a hazardous environmental pollutant, affecting Amazon basin communities by anthropogenic activities. The exact safe level of MeHg exposure is unclear, despite the efforts of health international societies to avoid mercury (Hg) poisoning. Central nervous system is severely impacted by Hg intoxication, reflecting on motor impairment. In addition, alcohol has been associated to an overall brain damage. According to lifestyle of Amazon riverside communities, alcohol intake occurs frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 66 publications
4
19
0
Order By: Relevance
“…Moreover, at the beam walking test, animals that consumed alcohol presented worse motor performance characterized by higher number of falls and less ability for activities that required motor dexterity. These results corroborate those recently found in another study from our group, which demonstrated that binge episodes during adolescence impact motor performance [50, 52], as well as affect other brain areas, inducing an anxiogenic behavior and influencing short-term recognition memory [6]. We believe that ethanol consumption increased cerebral blood flow by increasing the metabolic oxygen demand, so that brain regions related to motor activity and central command network are affected.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, at the beam walking test, animals that consumed alcohol presented worse motor performance characterized by higher number of falls and less ability for activities that required motor dexterity. These results corroborate those recently found in another study from our group, which demonstrated that binge episodes during adolescence impact motor performance [50, 52], as well as affect other brain areas, inducing an anxiogenic behavior and influencing short-term recognition memory [6]. We believe that ethanol consumption increased cerebral blood flow by increasing the metabolic oxygen demand, so that brain regions related to motor activity and central command network are affected.…”
Section: Discussionsupporting
confidence: 92%
“…Actually, the performance in the open field test is mainly related to the motor cortex [46]. In previous works with chronic exposure to MeHg, we demonstrated that mercury seems to be less present in the motor cortex and hippocampus in comparison with other areas of the brain, such as prefrontal cortex and cerebellum, of exposed animals [47,48]. In this sense, our hypothesis is that even with higher doses of MeHg, the four-days exposure in adult male mice used in this work is not sufficient to affect the motor cortex to produce significant changes in spontaneous exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Animals that failed to turn, in other words, slid across the beam in the same position as they were placed on the equipment, or fell, even if they had already turned upside down, were given the maximum time (120 s). The average was calculated with the 3 best times of each animal [ 72 , 76 ].…”
Section: Methodsmentioning
confidence: 99%